Socio-Economic Factors That Influence Poverty Levels In Medan City, North Sumatra Province - Dhea Nita Syafina Rambe; Irsad Lubis (Journal of Research in Social Science and Humanities, 2025)
Poverty be one of size most important For know level welfare something House stairs. As something size aggregate, level poverty in a region is common used For measure level welfare in the region. With thus, poverty be one of matter main development economy. The size amount resident the potential create problem complex social, such as decline quality source Power humans, increasing level poverty, the emergence of inequality and jealousy social, disruption stability social politics, increasing number crime and its impacts others. If the condition the ongoing Keep going continuously, then in turn can hinder development the economy of Medan City so that make things difficult the realization of a dignified, prosperous and just Medan City. Variables in study This in the form of index development, growth economy, level wages, level unemployment become factor affecting level poverty. Processed data with Then use multiple linear regression. The data obtained processed from BPS with using SPSS software Version 23. Multiple linear regression results can seen that adjusted R Square figure of 0.612 which can called coefficient deep determination matter This meaning 61.2% of poverty in Medan City, can be obtained and explained by the HDI, GDP, wages and unemployment, while the remaining 38.8% is explained by other factors or variables outside the model that is not researched.